Penggunaan Model Pembelajaran Make A Match debagai Upaya Meningkatkan Prestasi Belajar Siswa dalam Pembelajaran PAI Pada Kelas VII.2 di SMP Negri 2 Simpang Alahan Mati - Norawati Norawati; Dinanda TJ Menanti (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
This research was conducted at SMP Negeri 2 Simpang Alahan Mati in class VII.2 . with a total of 27 student, consisting of 15 male students and 12 famale students were studied. The study was conduced academic year from february 13 to march 13, 2024. action research is to find out whether the Make A Match learning model can improve student learning achievement. The data collection method is a learning achievement test. The data analysis method is descriptive for both qualitative and quantitative data. The results obtained from this study are that the Make A Match learning model can improve student learning achievement. This is evident from the results in cycle I reaching an average value of 74.52 with a learning completion percentage of 70%, and in cycle II reaching an average value of 80.59 with a learning completion percentage of 89%. The conclusion obtained from this study is that the Make A Match learning model can improve the Islamic Religious Education learning achievement of class VII.2 students at SMP Negeri 2 Alahan Mati.